Hubungan Komunikasi Interpersonal Dan Kinerja Raffles Service Agent Pada Hotel Raffles Jakarta - Susilowati Susilowati; Aditya Pratomo (Cakrawala - Jurnal Humaniora, 2022)
An organization in its activities really needs communication with many employees, leaders and even consumers, then interpersonal communication is needed, because interpersonal communication is personal communication from one person to another and can build positive relationships and improve employee performance. The purpose of this study was to determine the relationship and influence of interpersonal communication on the performance of the Raffles Service Agent at the Raffles Hotel Jakarta. The analysis used in this research is descriptive analysis and simple linear regression analysis. SPSS version 25 is used to measure validity, reliability, descriptive analysis, correlation analysis, simple regression analysis. The results of this study indicate that there is a significant influence of interpersonal communication on the performance of Raffles Service Agent of 88.3% with a correlation of 0.940 which indicates there is a very strong relationship between the two variables. The conclusion obtained is that the performance of Raffles Service Agent will also increase if interpersonal communication is also improved. Keywords:Interpersonal Communication, Employee Performance, Front Office Department.